(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Hormones are chemical messengers of the body that regulate bodily functions. Symptoms like depression, anxiety, and fatigue are caused by hormones going out of balance. In this study, we built a system that diagnoses three hormone imbalances (Testosterone, Thyroid Hormone, and Cortisol Hormone). The system makes use of a knowledge base built using the Web Ontology Language (OWL) and it interacts with the knowledge base using Jena API because it provides an ontology API for connecting to the ontology, generic reasoner serving as the inference engine, and SPARQL implementation for performing statistical queries. The benefits of this approach over an existing expert based system are improved ontology model by 71% in terms of knowledge representation and 58% in terms of taxonomy, ability to share patient data by moving them from MySQL database into the ontology, and ability to diagnose three related hormone imbalances